Integrating TRPV1 Receptor Function with Capsaicin Psychophysics - Gregory Smutzer; Roni K. Devassy (Hindawi Limited, 2016)
Capsaicin is a naturally occurring vanilloid that causes a hot, pungent sensation in the human oral cavity. This trigeminal stimulus activates TRPV1 receptors and stimulates an influx of cations into sensory cells. TRPV1 receptors function as homotetramers that also respond to heat, proinflammatory substances, lipoxygenase products, resiniferatoxin, endocannabinoids, protons, and peptide toxins. Kinase-mediated phosphorylation of TRPV1 leads to increased sensitivity to both chemical and thermal stimuli. In contrast, desensitization occurs via a calcium-dependent mechanism that results in receptor dephosphorylation. Human psychophysical studies have shown that capsaicin is detected at nanomole amounts and causes desensitization in the oral cavity. Psychophysical studies further indicate that desensitization can be temporarily reversed in the oral cavity if stimulation with capsaicin is resumed at short interstimulus intervals. Pretreatment of lingual epithelium with capsaicin modulates the perception of several primary taste qualities. Also, sweet taste stimuli may decrease the intensity of capsaicin perception in the oral cavity. In addition, capsaicin perception and hedonic responses may be modified by diet. Psychophysical studies with capsaicin are consistent with recent findings that have identified TRPV1 channel modulation by phosphorylation and interactions with membrane inositol phospholipids. Future studies will further clarify the importance of capsaicin and its receptor in human health and nutrition.